ANALISIS MANFAAT DAN KEPUASAN PESERTA WANITA PROGRAM PUSAT KEBUGARAN DI KOTA BOGOR - Julianti, Elisa Diana; Hartoyo, Hartoyo; Guhardja, Suprihatin (Jurnal Ilmu Keluarga dan Konsumen, 2008)
The objectives of the study were: to identify the socio economic characteristic of a female member, to analyze the expectancy and benefit of joining fitness center, to analyze the factors that influence the satisfaction of being member. The study was conducted in Bogor Municipality and purposive sampling was used to select 60 female member of fitness center who had been member for at least 2 months. The average age of the female was 30 years old and half of them were married. The proportion of an employed and unemployed female were equal, with the average income is about Rp 525,583.00. Most of them are senior high graduate and bachelor degree. The normal BMI of the respondents increased 11.1% (60% to 71.1%) after joining fitness center. To lose weight and to improve health condition were the reasons and expectations of most of the member. The Chi Square test showed that the expectations had a positive association with age and BMI, and no association with marital status. The benefits of joining the fitness center were improved health condition and endurance, lose weight, and have more friends. The study also found that respondent attitude significantly affects the satisfaction of joining fitness center.